Ecological risks in downstream lakes exacerbated by the three Gorges reservoir - Xinxin Chen; Yaxin Guo; Junhong Zhang; Xiao Han; Weiya Huang; Yao Yue (Ecological Indicators)
River regulation through reservoir construction is one of the greatest challenges to the natural flow state and ecological health of river systems globally. The Three Gorges Dam (TGD), the largest dam in the world, has been in operation since 2003 to regulate water resources downstream. However, most of the current research on the TGD compares the post-2003 hydrologic patterns downstream of the TGD with the pre-2003 hydrologic patterns and lacks direct evidence of the TGD impacts on the downstream areas. In this paper, the ecological impacts of TGD on downstream large lakes are explored in terms of hydrological alteration degree, biodiversity, connectivity, and ecological surplus and ecological deficit by building a 1/2-dimensional nested model to simulate the hydrological processes with and without the TGD from 2008 to 2011. The results showed that (1) TGD storage led to a decrease in the number of high pulses at downstream stations, resulting in wetland degradation in the riverine region; (2) the SI (Shannon’s diversity index) based on hydrological calculations became smaller, indicating that the downstream biodiversity showed a decreasing trend; (3) the diversion ratio and the confluence ratio of Dongting Lake and the Yangtze River decreased at the same time, and the connectivity decreased, which would lead to an increase in the degree and frequency of droughts during the dry season;(4) after the regulation of the TGD, the low-risk months were transformed into medium-risk months of the Dongting Lake basin, indicating a deterioration of the ecological situation in this region. The study demonstrates that the construction of the TGD has exacerbated downstream water stress, while the degradation of wetlands and the reduction in biodiversity highlight the heightened pressure on ecological and environmental protection downstream of the TGD. The results of this study provide necessary information for evaluating the impact of the TGD project on large lakes downstream and provide feasible suggestions for water resource management and ecological protection in the Yangtze River basin to ensure the realization of sustainable development in the future.